PENDEKATAN HISTORIS: KRITIK SANAD, KRONOLOGI DAN MANUSKRIP - Saidek, Abdul Rahim; Nurkholisah; Febriansi, Ramadani; Izom, Fil; Egza, Fakhrurozi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines the historical approach in Islamic studies by focusing on three key methodological instruments: sanad criticism, chronology, and manuscript analysis. The problem addressed in this study is the persistence of ahistorical interpretations that treat historical products of Islamic thought as timeless and absolute, thereby limiting a contextual understanding of Islam. The objective of this study is to explain the nature of the historical approach, describe the processes involved in sanad criticism and chronological reconstruction, and analyze the role of manuscripts as material evidence in verifying textual authenticity. This study employs a qualitative descriptive method based on literature analysis of classical and modern scholarly works related to Islamic historiography and textual studies. The results indicate that sanad criticism functions as a systematic method to evaluate the credibility and accuracy of transmitters, chronological analysis helps reconstruct the development of Islamic law and intellectual traditions within their socio-historical context, and manuscript studies supported by philology and codicology provide objective material evidence that strengthens historical reconstruction. Therefore, the historical approach contributes to developing Islamic studies as a rigorous and scientific discipline grounded in verifiable data rather than assumptions.